Gambaran Keluhan Muskuloskeletal Pada Pegawai yang Menggunakan Personal Computer di Rsud Dr. Murjani Sampit - Rakhmad Rosadi; Yogi Antoniyus; Sri Sunaringsih Ika Wardojo; Yudha Wahyu Putra; Safun Rahmanto (LPPM Universitas Abdurrab, 2021)
Abstract: The use of computers requires good coordination between muscles, tendons and innervation so that they do not cause health problems. In addition, in operating computers, there is also interaction between individual workers / computer users and their work equipment, namely computer desks and chairs, where if there is a mismatch between work equipment and individual users, it can cause musculoskeletal complaints. This case report is located in dr. Murjani Sampit, Kotawaringin Timur, Kaliantan Tengah. The purpose of this case report is to know the description of musculoskeletal complaints in employees who use personal computers at dr. Murjani Sampit. The method used is to use the Nordic Body Map sheet to find out complaints on Musculoskeletal and the Brief Survey method for ergonomic risk assessment. A case study was conducted on 10 administrative staff and registration counter staff. Based on the results of the ergonomic risk assessment using the Brief Survey method, the highest work risk was in the back region with a score of 3. Most musculoskeletal complaints were due to work by administrative staff and staff at the registration counter of dr. Murjani Sampit was found at the waist as many as 10 people (100.0%) and was followed by complaints on the upper neck as many as 5 people (50.0%).